Epoxy resin composition, cured product and semiconductor device

The epoxy resin composition, featuring a specific blend of epoxy resin, amine-based hardener, and inorganic filler, addresses the challenge of insufficient underfilling in larger interposers by maintaining low viscosity at high temperatures, ensuring reliable semiconductor device performance.

JP2025063732APending Publication Date: 2025-04-16NAMICS CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023173160
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

As interposers in semiconductor devices increase in size to improve performance and multifunctionality, the filling of underfill gaps becomes insufficient, leading to air bubble generation during the filling process, due to the increased viscosity of the underfill at high temperatures.

Method used

An epoxy resin composition is developed containing a specific blend of epoxy resin (A), an amine-based hardener (B) comprising 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluenediamine, and an inorganic filler (C) with a high content of dimethylthiotoluenediamine, which maintains low viscosity even at high temperatures, thereby improving the filling properties.

Benefits of technology

The epoxy resin composition achieves a good stage life, allowing for effective underfilling of larger interposers without air bubble formation, and results in a highly reliable semiconductor device with improved thermal cycle resistance and package protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063732000002
    Figure 2025063732000002
  • Figure 2025063732000001
    Figure 2025063732000001
Patent Text Reader

Abstract

To provide: an epoxy composition having good stage life; further a cured product of the epoxy composition; a semiconductor device comprising the cured product; and a method for manufacturing the semiconductor device.SOLUTION: There is provided an epoxy resin composition which comprises an epoxy resin (A), an amine-based curing agent (B) an inorganic filler (C), wherein the amine-based curing agent (B) contains 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluene diamine.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin composition. More specifically, the present invention relates to an epoxy resin composition for semiconductor encapsulation, a cured product, a semiconductor device, and a method for producing a semiconductor device. [Background technology]

[0002] Semiconductor devices are required to have higher performance, more functions, and lower power consumption. Until now, the mainstream was SoC (System on chip), which increases the integration density of transistors on a single chip to provide all functions, but this has led to problems such as rising manufacturing costs and reduced yields due to larger chips. In response to this, SiP (System in package) has been introduced, which divides the system into multiple chips and then integrates them at a high density. In SiP, a substrate called a silicon interposer is introduced. A silicon interposer is placed on the package substrate, and multiple chips are arranged on it in close proximity to each other. In addition, a multilayer wiring circuit is formed on the upper side of the silicon interposer, and it is connected to the resin substrate on the lower side by TSV (Through-silicon via). Since active elements such as transistors are not formed on silicon interposers, it is easier to enlarge them than chips. Therefore, it has become mainstream to enlarge silicon interposers and mount more chips on them. In addition, various interposers, such as interposers with silicon embedded in molded resin, are being considered for further enlargement.

[0003] The interposer and the resin substrate are connected via bump electrodes. When a thermal load such as a temperature cycle is applied, the difference in the linear thermal expansion coefficient of each component places stress on the bump electrodes, which causes problems such as cracks in the bump electrodes. For this reason, the gap between the interposer and the resin substrate is sealed with a liquid sealing material called underfill, improving resistance to thermal loads (thermal cycle resistance) and the property of protecting the package from heat and external forces (package protection) (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-171754 A [Patent Document 2] JP 2016-108358 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, interposers have become larger in size in order to improve the performance and multi-function of semiconductor devices. However, when the interposer becomes larger, there are problems such as the underfill not filling the gaps sufficiently and air bubbles being generated due to the entrapment of air during filling.

[0006] In order to improve the filling property of the underfill, it is common to heat the substrate to reduce the viscosity of the underfill. It is believed that the above problems arise because the underfill is exposed to the stage temperature during filling for a long period of time, which causes the underfill's curing reaction to progress and the viscosity to increase. Therefore, in order to solve these problems, the epoxy composition is required to have a property that the viscosity does not easily increase even at high temperatures. Hereinafter, an epoxy composition having such a property may be expressed as having a "good stage life."

[0007] Therefore, an object of the present invention is to provide an epoxy composition having a good stage life, a cured product of the epoxy composition, a semiconductor device including the cured product, and a method for manufacturing the semiconductor device. [Means for solving the problem]

[0008] As a result of intensive research into achieving the above object, the present inventors have found that the above problems can be solved by using a composition having a specific structure. The present invention has been completed based on these findings.

[0009] That is, in the present invention, An epoxy resin (A); an amine-based curing agent (B); An epoxy resin composition comprising an inorganic filler (C), The epoxy resin composition is provided, wherein the amine-based curing agent (B) comprises 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluenediamine.

[0010] The content of dimethylthiotoluenediamine in the amine curing agent (B) is preferably 23 mass % or more.

[0011] The content of dimethylthiotoluenediamine in the amine curing agent (B) is preferably 28 mass % or more.

[0012] The content of dimethylthiotoluenediamine in the amine curing agent (B) is preferably 45 mass % or less.

[0013] The epoxy resin (A) preferably contains at least one selected from the group consisting of bisphenol type epoxy resins, naphthalene type epoxy resins, aminophenol type epoxy resins, cyclohexane type epoxy resins, and glycidylamine type epoxy resins.

[0014] The content of the inorganic filler (C) is preferably 50% by mass or more.

[0015] The epoxy resin composition is preferably used for semiconductor encapsulation.

[0016] The present invention also provides a cured product of the above epoxy resin composition.

[0017] In the present invention, A substrate; A semiconductor element disposed on the substrate; the cured product that encapsulates the semiconductor element; and A semiconductor device comprising the same is also provided.

[0018] In the present invention, A substrate; filling a gap between the semiconductor element disposed on the substrate and the substrate with the epoxy resin composition; curing the epoxy resin composition; A method for manufacturing a semiconductor device including the steps of: Effect of the Invention

[0019] The epoxy resin composition of the present invention has a good stage life. Therefore, even when a semiconductor device is manufactured using a substrate such as a large-sized interposer, the gap can be filled with underfill without any problems, and air bubbles are unlikely to occur. Furthermore, a semiconductor device having a cured product of the above epoxy composition exhibits high reliability because the semiconductor is sealed with high precision. [Brief description of the drawings]

[0020] [Figure 1] 1(a) to 1(c) are diagrams illustrating "Evaluation 3: Gap filling test" in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] (Epoxy resin composition) The epoxy resin composition contains an epoxy resin (A), an amine-based curing agent (B), and an inorganic filler (C). It may further contain one or more of the core-shell rubber particles (D), a curing accelerator (E), and a coupling agent (F) described below. It may also contain a curing agent other than the amine-based curing agent (B) (hereinafter referred to as "other curing agent").

[0022] Epoxy resin (A) The epoxy resin composition contains the epoxy resin (A) and can form a cured product with high electrical insulation. The number of epoxy groups in the epoxy resin (A) is not particularly limited as long as it is 1 or more, but is preferably 2 or more (i.e., a polyfunctional epoxy resin). The epoxy resin (A) can be used alone or in combination of two or more.

[0023] The epoxy resin (A) may be liquid or solid at room temperature (25° C.), but is preferably liquid from the viewpoint of the viscosity of the epoxy resin composition. A solid epoxy resin can also be preferably used when it is used in combination with a liquid epoxy resin to exhibit a liquid state as a mixture.

[0024] The epoxy resin (A) is not particularly limited, and examples thereof include bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, and bisphenol AF type epoxy resins, bixylenol type epoxy resins, cyclohexane type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins (glycidylamine type epoxy resins having no aromatic structure or glycidylamine type epoxy resins having an aromatic structure), glycidyl ester type epoxy resins (glycidyl ester type epoxy resins having no aromatic structure or glycidyl ester type epoxy resins having an aromatic structure), cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins (linear aliphatic epoxy resins having no aromatic structure), epoxy resin or linear aliphatic epoxy resin having an aromatic structure), epoxy resin having a butadiene structure (epoxy resin having a butadiene structure without an aromatic structure or epoxy resin having a butadiene structure with an aromatic structure), alicyclic epoxy resin (alicyclic epoxy resin having no aromatic structure or alicyclic epoxy resin having an aromatic structure), heterocyclic epoxy resin, spiro ring-containing epoxy resin (spiro ring-containing epoxy resin having no aromatic structure or spiro ring-containing epoxy resin having an aromatic structure), cyclohexane dimethanol type epoxy resin (cyclohexane dimethanol type epoxy resin having no aromatic structure or cyclohexane dimethanol type epoxy resin having an aromatic structure), naphthylene ether type epoxy resin, trimethylol type epoxy resin (trimethylol type epoxy resin having no aromatic structure or trimethylol type epoxy resin having an aromatic structure), tetraphenylmethane type epoxy resin, aminophenol type epoxy resin, and silicone modified epoxy resin, and other aromatic or aliphatic epoxy resins.

[0025] Among these, the epoxy resin (A) preferably contains at least one selected from the group consisting of bisphenol type epoxy resins, naphthalene type epoxy resins, aminophenol type epoxy resins, cyclohexane type epoxy resins, and glycidylamine type epoxy resins, and more preferably contains at least one selected from the group consisting of bisphenol F type epoxy resins, bisphenol A type epoxy resins, naphthalene type epoxy resins, aminophenol type epoxy resins, and cyclohexane type epoxy resins (particularly, 1,4-glycidylcyclohexane).

[0026] Specific examples of liquid epoxy resins include "YDF-8170" (bisphenol F type epoxy resin), "YDF-8125" (bisphenol A type epoxy resin), "ZX-1658", and "ZX-1658GS" (liquid 1,4-glycidylcyclohexane) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "HP-4032", "HP-4032D", and "HP-4032SS" (naphthalene type epoxy resin) manufactured by DIC Corporation; and "jER828US", "jER828EL" (bisphenol A type epoxy resin), "jER806", and "jER807" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation. Examples of epoxy resins include bisphenol F type epoxy resins), "jER152" (phenol novolac type epoxy resin), "jER630", "jER630LSD", "EP3980S" (aminophenol type epoxy resin), "YX7400" (high resilience epoxy resin), "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation, and "Celloxide 2021P" (alicyclic epoxy resin) manufactured by Daicel Corporation.

[0027] Specific examples of solid epoxy resins include "HP-4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200L", "HP-7200HH", "HP-7200H", "HP-7200HHH" (dicyclopentadiene type epoxy resin), "EXA7311", and "EXA7311-G" manufactured by DIC Corporation. 3", "EXA7311-G4", "EXA7311-G4S", "HP6000" (naphthylene ether type epoxy resin), "EPPN-502H" (trisphenol type epoxy resin), "NC-7000-L" (naphthol novolac type epoxy resin), "NC-3000-H", "NC-3000", "NC-3000-L", "NC-3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd., "ESN475V" (naphthol type epoxy resin), "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd. Novolac type epoxy resin), Mitsubishi Chemical Corporation's "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bixylenol type epoxy resin), "YL7760" (bisphenol AF type epoxy resin), "YX8800" (anthracene type epoxy resin), Osaka Gas Chemical Co., Ltd.'s "PG-100", "CG-500", Mitsubishi Chemical Corporation's "YL7800" (fluorene type epoxy resin), Mitsubishi Chemical Corporation's "jER1010" (solid bisphenol A type epoxy resin) resin), "jER1031S" (tetraphenylethane type epoxy resin), "jER157S70" (bisphenol novolac type epoxy resin), Mitsubishi Chemical Corporation's "YX4000HK" (bixylenol type epoxy resin) and "YX8800" (anthracene type epoxy resin), Osaka Gas Chemicals Co., Ltd.'s "PG-100" and "CG-500", Mitsubishi Chemical Corporation's "YL7800" (fluorene type epoxy resin), and Mitsubishi Chemical Corporation's "jER1031S" (tetraphenylethane type epoxy resin).

[0028] The epoxy equivalent of the epoxy resin (A) is not particularly limited, but is, for example, preferably 30 to 1000 g / eq, more preferably 40 to 500 g / eq, and further preferably 50 to 300 g / eq.

[0029] The content of the epoxy resin (A) relative to the epoxy resin composition (100% by mass) is not particularly limited, but is preferably 5% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and particularly preferably 12% by mass or more. Also, for example, it is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less, and particularly preferably 40% by mass or less. By having the content of the epoxy resin (A) within the above range, the thermal expansion of the cured product tends to be reduced and the toughness tends to be improved. In addition, the viscosity of the epoxy resin composition tends not to increase even at high temperatures.

[0030] Amine-based hardener (B) The amine-based curing agent (B) is an amine-based curing agent that initiates, advances, or accelerates the polymerization of the epoxy resin, and includes 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluenediamine. In the present invention, by including the above two components as the amine-based curing agent (B), the viscosity of the epoxy resin composition tends not to increase easily even at high temperatures.

[0031] Dimethylthiotoluenediamine has a feature that the distance between amino groups in the molecule is short compared to other amine-based curing agents such as 4,4'-methylenebis(2-ethylaniline). Therefore, when one amino group reacts to form a reactant during the curing reaction of an epoxy resin composition, the reactivity of the other amino group tends to decrease, possibly due to steric hindrance caused by the reactant. In addition, perhaps due to the bulkiness of the methylthio group, it tends to be less reactive than amine-based curing agents such as diethyltoluenediamine, which have a similar structure. For these reasons, dimethylthiotoluenediamine tends to be less reactive (in other words, to have a slower reaction rate) compared to other amine-based curing agents.

[0032] In the present invention, the inventors have discovered that by using a combination of 4,4'-methylenebis(2-ethylaniline), which has a relatively high reactivity, and dimethylthiotoluenediamine, which has a relatively low reactivity, it is possible to suppress thickening of an epoxy composition at high temperatures without impairing the properties that are originally required as a curing agent.

[0033] Examples of the amine curing agent (B) include, in addition to 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluenediamine, aromatic amines such as 4,4'-diamino-3,3'-diethyldiphenylmethane, diethyltoluenediamine, methylenedianiline, m-phenylenediamine, 4,4'-diaminodiphenylsulfone, and 3,3'-diaminodiphenylsulfone. These amine curing agents can be used alone or in combination of two or more.

[0034] The active hydrogen equivalent of the amine curing agent (B) is not particularly limited, but is, for example, preferably 10 to 300 g / eq, more preferably 20 to 160 g / eq, and further preferably 30 to 100 g / eq.

[0035] The content of the amine-based curing agent (B) is not particularly limited, but for example, the stoichiometric equivalent ratio (active hydrogen equivalent / epoxy group equivalent) with the epoxy resin (A) is preferably 0.5 to 1.5, and more preferably 0.8 to 1.2.

[0036] The content of dimethylthiotoluenediamine relative to the amine-based curing agent (B) (100% by mass) is not particularly limited, but is preferably 23% by mass or more, more preferably 25% by mass or more, even more preferably 28% by mass or more, and particularly preferably 30% by mass or more. The content is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less, and particularly preferably 40% by mass or less. If the content of dimethylthiotoluenediamine is more than 60% by weight, the Tg (glass transition temperature) after curing of the epoxy resin composition tends to be low, and there is a risk of impairing the heat resistance reliability. By having the content of dimethylthiotoluenediamine within the above range, the stage life of the epoxy resin composition tends to be better without impairing the Tg after curing. The tendency of improving the heat resistance reliability is more pronounced when the content of dimethylthiotoluenediamine is 50% by mass or less, and even more pronounced when it is 45% by mass or less.

[0037] The content ratio (mass ratio) of 4,4'-methylenebis(2-ethylaniline) to dimethylthiotoluenediamine is not particularly limited, but is, for example, preferably 77:23 to 50:60, more preferably 75:25 to 50:50, even more preferably 72:28 to 55:45, and still more preferably 70:30 to 60:40. When the content ratio is within the above range, the stage life of the epoxy resin composition tends to be better.

[0038] The content (total amount) of 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluenediamine in the amine curing agent (B) is not particularly limited, but is preferably 60 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and particularly preferably 95 mass% or more. When the content of 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluenediamine is within the above range, the stage life of the epoxy resin composition tends to be better.

[0039] The content of the amine-based curing agent (B) relative to the epoxy resin composition (100% by mass) is not particularly limited, but is preferably 2% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more. The content is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, and particularly preferably 12% by mass or less. When the content of the amine-based curing agent (B) is within the above range, the stage life of the epoxy resin composition tends to be better. In addition, the thermal expansion of the cured product tends to be reduced and the toughness tends to be improved.

[0040] Other hardeners The epoxy resin composition of the present invention may contain a curing agent other than the amine-based curing agent (B) (hereinafter referred to as "other curing agents"). Examples of the other curing agents include acid anhydride-based curing agents, phenol-based curing agents, and imidazole-based curing agents. The other curing agents may be used alone or in combination of two or more.

[0041] Examples of the acid anhydride-based hardener include alkylated tetrahydrophthalic anhydrides such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, phthalic anhydride, dodecenyl succinic anhydride, and methylnadic anhydride. Examples of the phenol-based hardener include phenol novolac resin, cresol novolac resin, naphthol-modified phenol resin, dicyclopentadiene-modified phenol resin, and p-xylene-modified phenol resin. Examples of the imidazole-based hardener include 2-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-imidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Further, the imidazole-based curing agent also includes a microencapsulated imidazole-based curing agent.

[0042] The content of the other curing agent relative to the above-mentioned epoxy resin composition (100 mass%) is not particularly limited, but is, for example, preferably 20 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, particularly preferably 1 mass% or less, and most preferably 0.1 mass% or less.

[0043] The content of the curing agent relative to the epoxy resin composition (100% by mass) is not particularly limited, but is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 5% by mass or more. The content is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less. When the content of the curing agent is within the above range, the thermal expansion of the cured product tends to be reduced and the toughness tends to be improved. Here, the "curing agent" refers to the total amount of the curing agent contained in the epoxy resin composition, specifically the total amount of the amine-based curing agent (B) and other curing agents.

[0044] ·Inorganic filler (C) The inorganic filler (C) is not particularly limited, but is preferably one that (1) has the property of suppressing volumetric shrinkage (cure shrinkage) caused by the curing reaction of the epoxy resin composition, (2) has the property of suppressing volumetric change due to heating of the cured product (thermal shrinkage), i.e., has the effect of lowering the linear expansion coefficient when added, or (3) has both of these properties.

[0045] Examples of the inorganic filler (C) include silica (silicon dioxide), silicon carbide, silicon nitride, alumina (aluminum oxide), aluminum nitride, aluminum hydroxide, aluminum silicate, magnesium silicate, calcium silicate, calcium carbonate, barium sulfate, barium carbonate, titanium oxide, lime sulfate, potassium titanate, magnesium carbonate, zinc oxide, boron nitride, zirconia (zirconium oxide), and inorganic particles having their surfaces treated. Among these, silica is preferred from the viewpoint of increasing the loading amount. The inorganic filler (C) can be used alone or in combination of two or more.

[0046] In order to keep the viscosity of the epoxy resin composition within an appropriate range, the inorganic filler (C) is preferably surface-treated with a coupling agent having a functional group such as an epoxy group, a (meth)acryloyl group, or an amino group (particularly a phenylamino group). Examples of the coupling agent include silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane. For the surface treatment of the inorganic filler (C), one of the above coupling agents can be used alone, or two or more can be used in combination.

[0047] The shape of the inorganic filler (C) is not particularly limited, and examples thereof include a spherical shape (such as a true spherical shape or a nearly true spherical shape), a polyhedral shape, a rod shape (such as a cylindrical shape or a prismatic shape), a flat plate shape, a scale shape, and an irregular shape. Among these, a spherical shape is preferred from the viewpoint of achieving a high loading amount.

[0048] The average particle size of the inorganic filler (C) is not particularly limited, but is preferably 1 nm to 10 μm, more preferably 0.1 to 5 μm, and more preferably 0.3 to 3 μm. By having the average particle size of the inorganic filler (C) in the above range, the viscosity of the epoxy resin composition is in an appropriate range, and the filling speed into the gap tends to be less likely to decrease. In addition, two or more fillers having different average particle sizes may be used in combination for the purpose of adjusting the viscosity of the epoxy resin composition. In this specification, the method for measuring the average particle size of the inorganic filler (C) is not particularly limited, but can be measured, for example, using a laser diffraction / scattering particle size distribution analyzer (product name: LS 13 320, manufactured by Beckman Coulter).

[0049] The content of the inorganic filler (C) relative to the epoxy resin composition (100% by mass) is not particularly limited, but is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 45% by mass or more, and most preferably 50% by mass or more. Although not particularly limited, it is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less. By having the content of the inorganic filler (C) within the above range, the stage life of the epoxy resin composition tends to be better. In addition, the curing shrinkage and heat shrinkage of the cured product tend to be suppressed.

[0050] Core-shell rubber particles (D) The core-shell rubber particles (D) have the effect of suppressing the occurrence and progression of fillet cracks when the epoxy resin composition is used as an underfill. Specifically, the incorporation of the core-shell rubber particles (D) reduces the elastic modulus of the cured product of the epoxy resin composition, thereby reducing the stress generated in the fillet portion and suppressing the occurrence of fillet cracks. In addition, when fillet cracks occur, the core-shell rubber particles (D) act as a stress relaxant and suppress the progression of the fillet cracks.

[0051] The core-shell rubber particles (D) refer to rubber particles composed of a core and one or more shell layers covering the core. The core-shell rubber particles (D) have a core composed of a material having excellent flexibility and a shell layer composed of a material having excellent affinity for the components contained in the epoxy resin composition, particularly the epoxy resin (A), and therefore exhibit good dispersibility in the epoxy resin composition and can achieve a low elastic modulus of the cured product.

[0052] In the core-shell rubber particles (D), the core part is formed of a material having excellent flexibility. Examples of the material forming the core part include silicone-based rubber, butadiene-based rubber, styrene-based rubber, acrylic rubber, polyolefin-based rubber, and silicone / acrylic composite rubber. The material forming the shell layer is preferably a material having excellent affinity with the components contained in the epoxy resin composition of the present invention (particularly, the epoxy resin (A)). Examples of the material forming the shell layer include epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, and glycidyl methacrylate, and acrylic resin. The core-shell rubber particles (D) can be used alone or in combination of two or more types.

[0053] Specific examples of the core-shell rubber particles (D) include "Kane Ace MX-153", "Kane Ace MX-257", "Kane Ace MX-154", "Kane Ace MX-960", "Kane Ace MX-136", "Kane Ace MX-137", "Kane Ace MX-965", "Kane Ace MX-217", "Kane Ace MX-227M75", "Kane Ace MX-334M75", "Kane Ace MX-416", and "Kane Ace MX-451" manufactured by Kaneka Corporation; "Metabrene C-223A", "Metabrene C-140A", "Metabrene E-860A", "Metabrene E-870A", "Metabrene E-875A", "Metabrene S-2100", "Metabrene S-2200", and "Metabrene S-2260" manufactured by Mitsubishi Chemical Corporation; and "Staphyloid" manufactured by Aica Kogyo Co., Ltd. Examples of such rubber particles include "Staphyloid IM-203", "Staphyloid IM-401", "Staphyloid IM-601", "Staphyloid AC3355", "Staphyloid AC3816", "Acryset BPA328" and "Acryset BPF307" manufactured by Nippon Shokubai Co., Ltd., and "EP 2240 A", "EP 5340", "PU 5640", "VE3340", and "XP1 / 0767" manufactured by EVONIC. In particular, from the viewpoints of toughness, heat resistance, durability, and crack resistance, silicone-based or butadiene-based core-shell rubber particles are preferred.

[0054] The content of the core-shell rubber particles (D) relative to the epoxy resin composition (100% by mass) is not particularly limited, but is preferably 0.3% by mass or more, more preferably 0.5% by mass or more. The content is also not particularly limited, but is preferably 10.0% by mass or less, more preferably 8.0% by mass or less.

[0055] Curing accelerator (E) The curing accelerator (E) has a property of promoting the curing of the epoxy resin. The curing accelerator is not particularly limited, but examples thereof include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Commercially available products include 2-phenyl-4-methylimidazole (manufactured by Shikoku Kasei Co., Ltd., trade name "2P4MZ"), 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine (manufactured by Shikoku Kasei Co., Ltd., trade name "2MZA"), and dicyandiamide. In addition, encapsulated imidazole, which is called microencapsulated imidazole or epoxy adduct imidazole, may be used. For example, "HX3941HP", "HXA3942HP", "HXA3922HP", "HXA3792", "HX3748", "HX3721", "HX3722", "HX3088", "HX3741", "HX3742", "HX3613" (all manufactured by Asahi Kasei Chemicals Corporation), "PN-23J", "PN-40J", "PN-50" (manufactured by Ajinomoto Fine-Techno Co., Ltd.), FXR-1121 (manufactured by Fuji Chemical Industry Co., Ltd.), etc. The curing accelerator (E) can be used alone or in combination of two or more kinds.

[0056] The content of the curing accelerator (E) relative to the epoxy resin composition (100% by mass) is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and is not particularly limited, but is preferably 5.0% by mass or less, more preferably 3.0% by mass or less.

[0057] Coupling agent (F) The coupling agent (F) is not particularly limited, and examples thereof include various coupling agents such as silane coupling agents such as vinyl, glycidoxy, methacryl, amino, mercapto, or imidazole coupling agents, titanium coupling agents such as alkoxide, chelate, or acylate coupling agents, and long-chain spacer coupling agents such as glycidoxyoctyltrimethoxysilane or methacrylooctyltrimethoxysilane. The coupling agent (F) may be used alone or in combination of two or more.

[0058] Examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane.

[0059] The content of the coupling agent (F) relative to the epoxy resin composition (100% by mass) is not particularly limited, but is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, for example. The content is also not particularly limited, but is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, for example.

[0060] Other ingredients (G) The epoxy resin composition may contain components other than the epoxy resin (A), the amine-based curing agent (B), the other curing agents, the inorganic filler (C), the core-shell rubber particles (D), the curing accelerator (E), and the coupling agent (F) (hereinafter referred to as "other components (G)"). Examples of the other components (G) include curable compounds other than the epoxy resin (A), thermoplastic resins such as polyethylene resins, polyester resins, polyurethane resins, and polyamide resins, ion trapping agents, leveling agents, antioxidants, defoamers, flame retardants, colorants, reactive diluents, elastomers, and solvents. The other components (G) may be used alone or in combination of two or more.

[0061] The content of the other component (G) relative to the epoxy resin composition (100% by mass) is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. Also, although not particularly limited, it is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more.

[0062] (Physical properties and production method of epoxy resin composition) The viscosity of the epoxy resin composition at 25°C is not particularly limited, but is preferably 0.1 to 300 Pa·s, more preferably 1 to 150 Pa·s, even more preferably 3 to 100 Pa·s, and particularly preferably 5 to 80 Pa·s. When the viscosity is within the above range, gap filling tends to be facilitated. The viscosity can be measured as the viscosity when rotated at 50 rpm for 1 minute at a liquid temperature of 25°C using a Brookfield viscometer (model number: HBDV-1, manufactured by Brookfield Corporation) as described in the Examples below.

[0063] The viscosity (initial viscosity) of the epoxy resin composition at 100°C is not particularly limited, but is preferably 0.001 to 5 Pa·s, more preferably 0.01 to 1 Pa·s, even more preferably 0.02 to 0.5 Pa·s, and particularly preferably 0.03 to 0.3 Pa·s. When the viscosity is within the above range, gap filling tends to be facilitated. The viscosity can be measured using a rheometer (HAAKE MARS60, Thermo Fisher Scientific) under the measurement conditions of 35 mm parallel plates, oscillation mode, and a frequency of 1 Hz, as described in the examples below. The initial viscosity means the viscosity within 3 minutes (particularly 30 seconds) after the start of measurement.

[0064] The viscosity of the epoxy resin composition at 100°C (viscosity after 1 hour) is not particularly limited, but is preferably 0.001 to 5 Pa·s, more preferably 0.01 to 1 Pa·s, more preferably 0.02 to 0.8 Pa·s, more preferably 0.03 to 0.6 Pa·s, more preferably 0.04 to 0.5 Pa·s, even more preferably 0.05 to 0.4 Pa·s, and particularly preferably 0.06 to 0.29 Pa·s. When the viscosity is within the above range, gap filling tends to be facilitated. The viscosity can be measured using a rheometer (HAAKE MARS60, Thermo Fisher Scientific) as described in the examples below, with 35 mm parallel plates, oscillation mode, and a frequency of 1 Hz as measurement conditions. The viscosity after 1 hour means the viscosity after 1 hour from the start of measurement.

[0065] In the epoxy resin composition, the viscosity increase rate (viscosity after 1 hour at 100°C / initial viscosity at 100°C), which can be calculated by dividing the "viscosity after 1 hour at 100°C" by the "initial viscosity at 100°C", is not particularly limited, and is, for example, preferably 1.0 to 4.8, more preferably 1.2 to 4, more preferably 1.3 to 3.5, more preferably 1.4 to 3.2, and even more preferably 1.5 to 2.8.

[0066] The epoxy resin composition can be prepared by a known and commonly used method. For example, the epoxy resin (A), the amine-based curing agent (B), and the inorganic filler (C), as well as at least one selected from the group consisting of other curing agents, core-shell rubber particles (D), curing accelerator (E), coupling agent (F), and other components (G) as required, are simultaneously or separately introduced into an appropriate mixer, and the epoxy resin composition can be obtained by stirring and mixing while melting by heating as required. When the epoxy resin (A) is solid, it is preferable to mix it after liquefying or fluidizing it by heating. When it is difficult to uniformly disperse the inorganic filler (C) in the epoxy resin composition, the epoxy resin (A) and the inorganic filler (C) may be heated and mixed to uniformly disperse the inorganic filler (C) in the epoxy resin (A), and then cooled as required, and further mixed with components such as the amine-based curing agent (B), to prepare the epoxy resin composition.

[0067] The mixer is not particularly limited, and examples thereof include a roll mill equipped with a stirrer and a heater, a Raikai mixer, a Henschel mixer, a tumbler, a planetary mixer, etc. The mixing ratio of each component is appropriately set according to the content of each component in the epoxy resin composition.

[0068] The epoxy resin composition can be preferably used as a material (semiconductor encapsulation epoxy resin composition) for encapsulating materials arranged on a substrate, such as a semiconductor element, wiring, and solder (solder bump) in a semiconductor device. By using the epoxy resin composition as a semiconductor encapsulation epoxy resin composition, a highly reliable encapsulated body can be manufactured. The epoxy resin composition can also be preferably used as a material (flip-chip type semiconductor encapsulation epoxy resin composition) for encapsulating a semiconductor element, etc. arranged on a substrate in a flip-chip type semiconductor device. Specifically, the epoxy resin composition is filled into the gap between a semiconductor element, etc. and a substrate, and then thermally cured, thereby encapsulating the bump electrode present in the gap, and fixing the semiconductor element and the substrate to each other as an encapsulated body, thereby improving thermal cycle resistance.

[0069] The epoxy resin composition for semiconductor encapsulation is used, for example, as an underfill such as a capillary underfill, a liquid mold underfill, a secondary underfill, or a pre-applied underfill, a grab top material, or a liquid compression molding material. The epoxy resin composition is not limited to the above-mentioned use as an epoxy resin composition for semiconductor encapsulation, and can be used, for example, as an adhesive for fixing, joining, or protecting components constituting an electronic component.

[0070] (Cured product and glass transition temperature (Tg) of epoxy resin composition) A cured product is formed by curing the epoxy resin composition. The curing method is not particularly limited, but for example, the epoxy resin composition is subjected to a heat treatment. The temperature of the heat treatment is not particularly limited, but for example, it is preferably 60 to 200°C, more preferably 80 to 180°C. The time of the heat treatment is not particularly limited, but for example, it is preferably 0.1 to 5 hours, more preferably 0.5 to 3 hours.

[0071] The glass transition temperature (Tg) of the cured product is not particularly limited, but is, for example, preferably 80 to 200° C., more preferably 90 to 190° C., further preferably 95 to 180° C., and particularly preferably 96 to 120° C. The glass transition temperature (Tg) can be measured, for example, by the method described in the Examples below. When the glass transition temperature measured by the above method is within the above range, the epoxy resin composition has a good stage life and the cured product has excellent heat resistance reliability.

[0072] (Semiconductor Device) The semiconductor device of the present invention comprises a substrate, a semiconductor element disposed on the substrate, and a cured product of the epoxy resin composition that seals the semiconductor element. The semiconductor device is preferably a flip-chip type semiconductor device. The flip-chip type semiconductor device has a structure in which an electrode portion on a substrate and a semiconductor element are connected via a bump electrode. In the semiconductor device, the gap between the semiconductor element and the substrate is sealed with a cured product (sealant) of the epoxy resin composition.

[0073] A semiconductor device can be manufactured by filling the gap between the substrate and the semiconductor element disposed on the substrate with the epoxy resin composition (filling step), and then heating and curing the epoxy resin composition (sealing step). The method of filling the gap with the epoxy resin composition is not particularly limited, but for example, the epoxy resin composition is applied to one end of the substrate or the semiconductor element while heating the substrate to 50 to 120°C, and the epoxy resin composition is filled into the gap between the substrate and the semiconductor element by capillary action. After filling the gap with the epoxy resin composition, the substrate is heated at a predetermined temperature for a predetermined time, specifically, at the temperature and time described in the heat treatment for forming the cured product, to seal the gap. EXAMPLES

[0074] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0075] The epoxy resin compositions of Examples 1 to 9 and Comparative Example 1 were prepared by appropriately mixing the epoxy resin (A), amine-based curing agent (B), and inorganic filler (C), as well as one or more components selected from the group consisting of core-shell rubber particles (D), curing accelerator (E), coupling agent (F), and other components (G) as necessary, so as to obtain the blending ratios shown in Table 1. The numerical values ​​for each component in Table 1 indicate parts by mass.

[0076] Each component in Table 1 will be explained below. Epoxy resin (A) YDF-8170 (product name): Bisphenol F type epoxy resin, epoxy equivalent 160g / eq, liquid at 25℃, manufactured by Nippon Steel Chemical & Material Co., Ltd. jER630 (product name): Aminophenol type epoxy resin, epoxy equivalent 98g / eq, liquid at 25℃, manufactured by Mitsubishi Chemical Corporation HP-4032D (product name): Naphthalene-type epoxy resin, epoxy equivalent 140g / eq, liquid at 25℃, manufactured by DIC Corporation ZX-1658GS (product name): 1,4-glycidylcyclohexane, epoxy equivalent 135g / eq, liquid at 25℃, manufactured by Nippon Steel Chemical & Material Co., Ltd. Amine-based hardener (B) HD AA / Product name is "KAYAHARD AA": 4,4'-methylenebis(2-ethylaniline), manufactured by Nippon Kayaku Co., Ltd. Ethacure 100 (product name): Diethyltoluenediamine, manufactured by Albemarle Corporation Ethacure 300 (product name): Dimethylthiotoluenediamine, manufactured by Albemarle Corporation ·Inorganic filler (C) SE5050-SEJ (product name): average particle size 1.5 μm, 3-glycidoxypropyltrimethoxysilane, surface-treated silicon dioxide, manufactured by Admatechs Co., Ltd. SE1050-SEO (product name): average particle size 0.3 μm, 3-glycidoxypropyltrimethoxysilane, surface-treated silicon dioxide, manufactured by Admatechs Co., Ltd. YA010A-JGP (product name): Masterbatch of nano-silica with an average particle size of 10 nm and bisphenol F type epoxy resin (weight ratio of the former to the latter = 3:7), nano-silica surface-treated with 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, manufactured by Admatechs Co., Ltd. Core-shell rubber particles (D) MX-965 (product name): Masterbatch of silicone-based core-shell rubber particles and bisphenol-type epoxy resin (weight ratio of former: latter = 25:75), manufactured by Kaneka Corporation Curing accelerator (E) CG-1400 / Product name is "AMICURE CG-1400": Dicyandiamide, manufactured by Evonik Japan Co., Ltd. Coupling agent (F) KBM-403 (product name): 3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd. Other ingredients (G) TPP (product name): Triphenylphosphine, manufactured by Hokko Chemical Co., Ltd. Special Black 4 powder (product name): Carbon black, manufactured by Orion Engineered Carbon Co., Ltd. Irganox 1010 (product name): Pentaerythritol tetrakis[3-[3,5-di(tert-butyl)-4-hydroxyphenyl]propionate], antioxidant, manufactured by BASF Japan Ltd. IXE500 (product name): Bismuth-based compound, ion trapping agent, manufactured by Toagosei Co., Ltd.

[0077] (Evaluation 1: Viscosity measurement at 25°C) The viscosity (Pa s) at 25°C immediately after preparation of the epoxy resin compositions of Examples 1 to 9 and Comparative Example 1 was measured using a Brookfield viscometer (model number: HBDV-1, manufactured by Brookfield) at a liquid temperature of 25°C and rotated at 50 rpm for 1 minute. The results are shown in the "25°C viscosity (Pa s)" section of the evaluation results in Table 1.

[0078] (Evaluation 2: Viscosity measurement at 100℃ / initial viscosity, viscosity after 1 hour, viscosity increase rate) The viscosity (initial viscosity, unit: Pa s) at 100°C immediately after preparation of the epoxy resin compositions of Examples 1 to 9 and Comparative Example 1 was measured using a rheometer (HAAKE MARS60, manufactured by Thermo Fisher Scientific). The measurement conditions were 35 mm parallel plates, oscillation mode, and a frequency of 1 Hz. The value 30 seconds after the start of the measurement was taken as the initial viscosity. The results are shown in Table 1 under "100°C initial viscosity (Pa s)." In the same manner as above, the viscosity value one hour after the start of measurement is recorded in Table 1 under "Viscosity after 1 hour at 100°C (Pa·s)". Furthermore, the viscosity after 1 hour was divided by the initial viscosity to obtain the viscosity increase rate. The results are shown in the "Viscosity increase rate" column of Table 1.

[0079] (Evaluation 3: Gap filling test) - Preparation of test specimens A tape was sandwiched between two glass slides so that the gap between them was 50 μm, and the glass slides were shifted by 1 cm to ensure the area where the evaluation sample was applied, thereby obtaining a test piece.

[0080] Testing and evaluation The above test piece was placed on a hot plate set at 100°C, and approximately 1 g of the epoxy resin composition of Examples 1 to 9 and Comparative Example 1 was applied to the sample application portion, and the time (min) until the filling distance reached 70 mm was measured.

[0081] The gap filling test will be described with reference to FIG. 1. In FIG. 1, 1 indicates a test piece. 2 and 2' are glass slides. 3 is a tape. 4 is a gap. 5 is an evaluation sample. (a) is a plan view of the test piece 1, with the longitudinal direction of the test piece 1 being vertical and the lateral direction being horizontal. (b) is a side view of the test piece 1 from the longitudinal direction. (c) is a side view of the test piece 1 from the lateral direction. The glass slide 2 is laminated with the other glass slide 2' via the tape 3. As shown in (b), the glass slide 2 and the glass slide 2' are laminated so that there is a 1 cm shift in the longitudinal direction. This shift is the application part (sample application part) of the evaluation sample 5. The gap 4 is a space surrounded by the glass slide 2 on its upper surface, the glass slide 2' on its lower surface, and two tapes 3 on its sides. In the gap 4, the distance between the glass slide 2 and the glass slide 2' is 50 μm, and the distance between the two tapes 3 is 10 mm. The longitudinal distance of the gap 4 is 70 mm. The test piece 1 is placed on a hot plate (not shown), and the evaluation sample 5 is applied to the sample application portion. The applied evaluation sample 5 moves downward through the gap 4 (a) due to capillary action. The time at which the evaluation sample 5 reaches the end of the slide glass 2' is measured and recorded in "Gap filling test (min)" in Table 1. The unit is minutes.

[0082] (Evaluation 4: Measurement of glass transition temperature (Tg)) A dynamic viscoelasticity device was used to measure the storage modulus (E') and loss modulus (E'') of the cured products of the epoxy resin compositions of Examples 1 to 9 and Comparative Example 1, and the peak value of tan δ, which is the ratio of these values, was determined as the glass transition temperature (Tg). The above measurements were performed in accordance with Japanese Industrial Standard JIS C6481.

[0083] More specifically, a Teflon (registered trademark) sheet was first attached to the surface of a 3 mm thick glass plate, and spacers (heat-resistant tape laminated thereon) were placed in two places so that the film thickness of the cured product was 2000±100 μm. Next, an epoxy resin composition was applied between the spacers, and the sheet was sandwiched between another glass plate with a Teflon (registered trademark) sheet attached to the surface so as not to trap air bubbles, and cured at 165°C for 2 hours to obtain a cured product. Finally, the cured product was peeled off from the glass plate with the Teflon (registered trademark) sheet attached, and then cut into a predetermined size (10 mm x 50 mm) with a cutting machine to obtain a test piece. The glass transition temperature (Tg) of this test piece was measured using a dynamic thermomechanical measurement device (DMA) (DMA7100, Hitachi High-Tech Science Corporation) in the range of -60°C to 260°C, a frequency of 1 Hz, a heating rate of 3°C / min, and a double-support bending method. Tg was calculated from the peak temperature (° C.) of tan δ calculated from E″ / E′. The results are shown in “Glass transition temperature (Tg)” in Table 1.

[0084] [Table 1] [Explanation of symbols]

[0085] 1 Test piece 2. Slides 2' Slide 3. Tape 4. Gap 5 Evaluation sample

Claims

1. An epoxy resin (A), An amine-based curing agent (B); An epoxy resin composition comprising an inorganic filler (C), An epoxy resin composition, wherein the amine-based curing agent (B) comprises 4,4'-methylenebis(2-ethylaniline) and dimethylthiotoluenediamine.

2. 2. The epoxy resin composition according to claim 1, wherein the content of dimethylthiotoluenediamine relative to the amine curing agent (B) is 23 mass% or more.

3. 3. The epoxy resin composition according to claim 1, wherein the content of dimethylthiotoluenediamine relative to the amine curing agent (B) is 28 mass% or more.

4. 3. The epoxy resin composition according to claim 1, wherein the content of dimethylthiotoluenediamine relative to the amine-based curing agent (B) is 45 mass% or less.

5. 3. The epoxy resin composition according to claim 1, wherein the epoxy resin (A) comprises at least one selected from the group consisting of bisphenol-type epoxy resins, naphthalene-type epoxy resins, aminophenol-type epoxy resins, cyclohexane-type epoxy resins, and glycidylamine-type epoxy resins.

6. 3. The epoxy resin composition according to claim 1, wherein the content of the inorganic filler (C) is 50 mass% or more.

7. 3. The epoxy resin composition according to claim 1, which is used for encapsulating a semiconductor.

8. A cured product of the epoxy resin composition according to claim 1 or 2.

9. A substrate; A semiconductor element disposed on the substrate; The cured product according to claim 8 which encapsulates the semiconductor element; A semiconductor device comprising:

10. A step of filling a gap between a substrate and a semiconductor element disposed on the substrate with the epoxy resin composition according to claim 1 or 2; a step of heating and curing the epoxy resin composition; A method for manufacturing a semiconductor device comprising the steps of:

Citation Information

Patent Citations

  • Liquid encapsulation material for copper bump and resin composition used for the same

    JP2016108358A

  • Epoxy resin composition, underfill agent, cured product, and semiconductor device

    JP2017171754A